'Tuning Out' or 'Tuning in'? Mobile Music Listening and Intensified Encounters with the City. (4th February 2017) - Watson, Allan; Drakeford‐Allen, Dominiqua
Abstract: Mobile music listening has become an increasingly pervasive part of urban life. Yet it represents an area of enquiry with which urban studies scholars have yet to engage meaningfully. This essay considers the role of mobile music devices in creating new sonic, emotional and social interactions with and within the city. While academic work in this area has emphasized the use of these devices as a 'tuning out' of the physicality of the city, we suggest that they might also be used as part of a 'tuning in' that enhances the meaning and intensity of engagements with the city. In making this case, the essay considers two areas of academic enquiry that highlight the use of mobile music devices in intensified engagements with the city: first, recent writing on the sonic ecologies of the city that emphasize 'city sounds' as part of the urban experience; and secondly, recent advances in the field of urban computing that provide technologies for location‐aware music exchanges and mediated social interactions. The essay emphasizes mobile music listening as one area of critical enquiry that can help develop our understanding of the ways in which the pervasiveness of mobile devices is recalibrating the experience of urban spatiality.